SMARTGPS android app / Mohd Nor Asnawi Abdul Jabar - Abdul Jabar, Mohd Nor Asnawi (2016)
Nowadays, smartphones are really a trend because each smartphones have multiple features that useful for different people’s needs. One of the useful features is Global Positioning System (GPS). This technology is really helpful especially in finding exact location the one who using the device. Vehicle Unit UiTM Shah Alam is under the governance of the Division of Student Affairs responsible for providing specialized transport facilities to students and staffs. In order for Vehicle Unit’s driver to have an efficient work is to follow the order from the manager. But, sometimes the driver can cheat when the manager asking about the driver current location thus decreasing the trust between employee and employer. SmartGPS will be installed in the driver’s smartphone while SmartGPSManager will be installed in manager’s smartphone.